2021
DOI: 10.1523/jneurosci.0592-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Respiration, Heartbeat, and Conscious Tactile Perception

Abstract: Previous studies have shown that timing of sensory stimulation during the cardiac cycle interacts with perception. Given the natural coupling of respiration and cardiac activity, we investigated here their joint effects on tactile perception. Forty-one healthy female and male human participants reported conscious perception of finger near-threshold electrical pulses (33% null trials) and decision confidence while electrocardiography, respiratory activity, and finger photoplethysmography were recorded. Particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 61 publications
(69 reference statements)
2
69
1
Order By: Relevance
“…Further, to the extent that interoceptive signals (as modeled by the brain) act as control signals for allostasis (Sennesh et al, 2021), those signals may also play a role in the sampling of unanticipated exteroceptive signals (i.e., exteroceptive prediction errors). This hypothesis is supported by evidence that sampling of visual, auditory, and other data from the sensory surfaces of the body is statistically related to bodily signals such as heart beats and respiration (e.g., Al et al, 2020;Aspell et al, 2013;Galvez-Pol et al, 2020;Grund et al, 2021;Kluger et al, 2021;Kunzendorf et al, 2019;Zelano et al, 2016).…”
Section: The Brain's Intrinsic System For Allostasismentioning
confidence: 90%
“…Further, to the extent that interoceptive signals (as modeled by the brain) act as control signals for allostasis (Sennesh et al, 2021), those signals may also play a role in the sampling of unanticipated exteroceptive signals (i.e., exteroceptive prediction errors). This hypothesis is supported by evidence that sampling of visual, auditory, and other data from the sensory surfaces of the body is statistically related to bodily signals such as heart beats and respiration (e.g., Al et al, 2020;Aspell et al, 2013;Galvez-Pol et al, 2020;Grund et al, 2021;Kluger et al, 2021;Kunzendorf et al, 2019;Zelano et al, 2016).…”
Section: The Brain's Intrinsic System For Allostasismentioning
confidence: 90%
“…Importantly, they freely initiated, held, and ended the sensing of the stimuli. From an interoceptive inference framework, studies in passive sensing have shown that tactile sensitivity is reduced during the systole phase of the cardiac cycle (Al, Iliopoulos, et al, 2021;Grund et al, 2022;Motyka et al, 2019). Hence, to avoid this drop in sensitivity, participants could circumvent the sampling of information in systole.…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysiological studies and analyses of cardio-sensory processing usually involve sample sizes on the order of 30-45 participants (Al et al, 2020; Galvez-Pol et al, 2020; Grund et al, 2022; Herman & Tsakiris, 2021; Kunzendorf et al, 2019; Motyka et al, 2019). Accordingly, we recruited 50 healthy adults (32 females; age range = 18-35) who participated in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations